Heterogeneity in glacier thinning and slowdown of ice movement in the Garhwal Himalaya, India - Bhambri, Rakesh; Schmidt, Susanne; Chand, Pritam; Nüsser, Marcus; Haritashya, Umesh; Sain, Kalachand; Tiwari, Sameer K.; Yadav, Jairam Singh (The science of the total environment, 2023)
Limited ground-based surveys and extensive remote sensing analyses have confirmed glacier thinning in the Garhwal Himalaya. More detailed studies on specific glaciers and the drivers of reported changes are essential to comprehend small-scale differences in the effects of climatic warming on Himalayan glaciers. We computed elevation changes and surface flow distribution for 205 (≥0.1 km2) glaciers in the Alaknanda, Bhagirathi, and Mandakini basins, all located in the Garhwal Himalaya, India. This study also investigates a detailed integrated analysis of elevation changes and surface flow velocities for 23 glaciers with varying characteristics to understand the impact of ice thickness loss on overall glacier dynamics. We observed significant heterogeneity in glacier thinning and surface flow velocity patterns using temporal DEMs and optical satellite images with ground-based verification. The average thinning rate was found to be 0.07 ± 0.09 m a-1 from 2000 to 2015, and it increased to 0.31 ± 0.19 m a-1 from 2015 to 2020, with pronounced differences between individual glaciers. Between 2000 and 2015, Gangotri Glacier thinned nearly twice as much as the neighbouring Chorabari and Companion glaciers, which have thicker supraglacial debris that protects the beneath ice from melting. The transitional zone between debris-covered and clean ice glaciers showed substantial flow during the observation period. However, the lower reaches of their debris-covered terminus areas are almost stagnant. These glaciers experienced a significant slowdown (~25 %) between 1993-1994 and 2020-2021, and only the Gangotri Glacier was active even in its terminus region during most observational periods. The decreasing surface gradient reduces the driving stress and causes slow-down surface flow velocities and an increase in stagnant ice. Surface lowering of these glaciers may have substantial long-term impacts on downstream communities and lowland populations, including more frequent cryospheric hazards, which may threaten future water and livelihood security.